A Study on the Causes, Complications, and Risk Factors of Polycystic Ovarian Syndrome Among Married Women in the Cuddalore District. - Mrs. A. PONMALAR; Dr. S. VASUKI (The Bioscan, 2026)
Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder among women of reproductive age and is a major contributor to subfertility associated with anovulation. Moreover, insufficient awareness of PCOS, its management, and the lifestyle modifications required for effective control adversely affects health outcomes. This qualitative study examines married women's understanding and perceptions of the syndrome, its treatment options, and the lifestyle changes necessary for its management. A total of 140 married women with PCOS were selected through convenience sampling from the Cuddalore District. The emerging themes encompassed women’s understanding of PCOS, its causes, complications, and associated risk factors. Keywords Polycystic Ovarian Syndrome, Lifestyle, Risk Factors, Causes, Complications, Reproductive Age.